The management decisions in government management structure of physical training - Lu Chzyshuan; Ivan Prikhodko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: is to improve the technology of management decision as for the function of making decision in the problem of choosing the variant. Material and Methods: analysis of scientific sources, analysis of the documents, organizational analysis. Results: different forms of management decisions are done, the structure of the decisions in the forms of orders are offered, the orders that are created due to the regional management structure are analysed, the quantity of fulfilled orders are shown, the reasons of unfulfilled orders are observed, the typical decisions of the orders and their corrections are done. Conclusions: the necessity of making the decisions are explained by conscious and aimed character of human's activity. The improvement of making the management decisions are done according to the use of scientific approach, different models and methods of making decisions in the management structure of physical training and sport.